THE EFFECT OF PERFORMANCE APPRAISAL AND ORGANIZATIONAL CULTURE ON PROMOTION OPPORTUNITIES FOR OUTSTANDING EMPLOYEES - Yenny Oktaviani; Putri Handayani (ZILLZELL MEDIA PRIMA, 2025)
Employee promotion plays a crucial role in career development and organizational success. Two primary factors influencing promotion opportunities are performance appraisal and organizational culture. Performance appraisal serves as a systematic process for evaluating employee contributions, while organizational culture shapes how these evaluations translate into promotion decisions. This study aims to examine the relationship between these factors and their impact on career advancement for outstanding employees. Using qualitative methods, this research investigates how appraisal systems and workplace culture interact to create or hinder promotion opportunities. The results suggest that transparent, merit-based performance appraisal systems, coupled with a supportive organizational culture, significantly enhance promotion prospects for top-performing employees. Organizations that foster fairness, clear evaluation criteria, and growth-oriented cultures are more likely to retain and advance high-potential talent.